Menumbuhkan Minat Berwirausaha Mahasiswa Melalui Kecerdasan Emosional - siti halimah; Hindra Wanto; Mahmu’ddin Mahmu’ddin (LP2M IAIN Palangka Raya, 2018)
This study was conducted to determine the effect of emotional intelligence on students’ entrepreneurship interest at semester VI Department of Information Systems Study Program Information System of Sampit Darwan Ali University Academic Year 2016/2017. This study used quantitative methods using survey technique. The subjects of the study were 92 students. Data collection techniques use a questionnaire fulfilled the requirements of validity and reliability. The technique of validity test used correlated item-total correlation and reliability test of Cronbach's alpha. In this study, the instrument used was questionnaire by using the likert scale. The data analysis technique used was a simple linear regression analysis fulfilled the analytical prerequisite, such as the test of normality, linearity and autocorrelation. This study revealed that emotional intelligence was moderate 70.65% and entrepreneurship interests were also moderate 67.39%. The result of analysis showed that there was an influence of emotional intelligence to student entrepreneur interest. Coefficient of determination (r2) was 0.265. It meant that emotional intelligence could foster interest in entrepreneurship student.